Enhancing Communication Skills for Akademi Digital Lansia Facilitators through Online Training in Makassar and Kendari - Citra Rosalyn Anwar; Rita Gani; Wiguna, King Anugrah; Yohannes Adven Sarbani; Niken Puppy Setyawati (Jogjakarta Communication Conference (JCC), 2025)
Online classes are a training approach that utilizes technology to increase training effectiveness, flexibility and interactiveness, at formal and non-formal education levels. This article explored communication skills in optimizing the Tular Nalar Training of Trainers (ToT) digital class. In the context of ToT, the Tular Nalar online class allowed prospective facilitators to participate directly via virtual space, the material could be accessed at any time and was equipped with interaction via WhatsApp groups. The Tular Nalar ToT program aimed to produce Sekolah Kebangsaan Facilitators and Akademi Digital Lansia, which was held in 38 provinces in Indonesia. January 2025 noted that ToT involved 3,481 participants who took part in online training to become facilitators who would deliver material about the Tular Nalar Program. This article used a qualitative descriptive approach in two cities, Makassar and Kendari, especially in the implementation of Akademi Digital Lansia. The in-depth interviews and observations in this article provided an analysis and description of the communication challenges of trainers and potential facilitators during ToT in online classes. Technological barriers, materials provided, and interactions required to ensure that facilitators were competent in delivering Akademi Digital Lansia materials. Prospective facilitators also face time differences during ToT, lack of interaction, limited discussion space, and material that was not fully understood. Interestingly, with these various limitations, these problems could be overcome with open interaction and good communication between trainers via WhatsApp, both individually and in groups. This showed that every facilitator and trainer needed to develop communication skills, local context, and technological support to become a good facilitator in implementing Akademi Digital Lansia Program.